Cluster Synchronization of Linearly Coupled Complex Networks Under Pinning Control - Wei Wu, Wei Wu; Wenjuan Zhou, Wenjuan Zhou; Tianping Chen, Tianping Chen (IEEE transactions on circuits and systems. I, Regular papers, 2009)
In this paper, we focus on the problem of driving a general network to a selected cluster synchronization pattern by means of a pinning control strategy. Sufficient conditions are presented to guarantee the realization of the cluster synchronization pattern for all initial values. We also show the detailed steps on how to construct the coupling matrix and to modify the control strengths. Moreover, the method of adapting the coupling strength is provided to refine the result.